Pain Imaging in the Emerging Era of Molecular Medicine - Stohler, Christian S. (2010)
With the dawn of the 21(st) Century, imaging has assumed a new role in disease-oriented science. Regarding pain, the emphasis clearly turned from structural to functional imaging with functional molecular imaging assuming the leading edge. This trend parallels the efforts of biologists working to understand the molecular messages of cell and cell systems’ of relevance to human disease processes. While originally imaging has been a stand-alone, documentary tool, today’s metabolic and molecular imaging technologies provide quantitative insight into inter-and intra-individual pathogenetic processes of relevance to human disease, complementing and expanding upon bench-type research. Imaging has become an indispensable tool in pain research.